Fabrication of α-mangostin – loaded liposomes for cytotoxic-activity against A549 lung-cancer spheroids - Tran Dinh Thiet,; Pham Thu Uyen,; Nguyen Thanh Duong, (Vietnam Journal of Science and Technology, 2023)
α-mangostin is a natural product isolated from the mangosteen pericarps with diverse biological activities, including cytotoxicity against cancer cells. However, the application of α-mangostin in cancer treatment is limited due to the high cytotoxicity and poor solubility in water. In this research, we fabricated α-mangostin-loaded liposomes from soybean lecithin and cholesterol to enhance the solubility in water of α-mangostin and reduce side effects in the treatment of cancer. The liposomal membrane uses Soybean Lecithin (SBL) as a phospholipid and Tocopherol (Toc) as a stabilizer, at 4 ratios of SBL/Toc are 1/1, 2/1, 4/1, 8/1. Experimental results showed that liposomes with SBL/Toc molar ratio of 4/1 had a mean size value of 105.8 ± 3.9 nm, and a polydispersity index (PDI) of 0.149. The encapsulation efficiency was 51.3 %. We believe that this formulation has the potential to be developed into an improved drug delivery system for α-mangostin. The lung carcinoma epithelial cells (A549) were cultured in microwell for 14 days to form spheroids. Then, spheroids were probed with a concentration of α-mangostin-loaded liposomes of 10 µM. The results showed the ability to significantly reduce cell viability after 36 hours of testing.